2017
DOI: 10.1158/1535-7163.mct-17-0061
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of Genomic Alterations by Next-Generation Sequencing in Tumor Tissue versus Circulating Tumor DNA in Breast Cancer

Abstract: While identifying genomic alterations in tumor tissue is the current gold-standard technique for molecular profiling, circulating tumor DNA (ctDNA) represents a noninvasive method of assessing genomic alterations using peripheral blood. The concordance of genomic alterations between two commercially available ctDNA and tissue biopsies was compared in 45 patients with breast cancer using paired next-generation sequencing tissue and ctDNA biopsies. Across all genes, concordance between the two platforms was 91.0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
93
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(120 citation statements)
references
References 44 publications
21
93
2
Order By: Relevance
“…Yao and colleagues (20) showed that the overall concordance rate of gene mutations between tissue DNA and ctDNA detection was 78.21% in patients with advanced non-small cell lung cancer. Another study indicated that the concordance of genomic alterations between tissue DNA and ctDNA was 91.0%-94.2% in breast cancer (21). Consistent with these previous studies, we obtained an overall concordance rate between ctDNA and tissue DNA detection of 71.9%, with moderate concordance.…”
Section: Discussionsupporting
confidence: 90%
“…Yao and colleagues (20) showed that the overall concordance rate of gene mutations between tissue DNA and ctDNA detection was 78.21% in patients with advanced non-small cell lung cancer. Another study indicated that the concordance of genomic alterations between tissue DNA and ctDNA was 91.0%-94.2% in breast cancer (21). Consistent with these previous studies, we obtained an overall concordance rate between ctDNA and tissue DNA detection of 71.9%, with moderate concordance.…”
Section: Discussionsupporting
confidence: 90%
“…Because tissue sequencing is still the 'gold standard' for molecular profiling of solid tumors, we evaluated the overall concordance of somatic alterations between tumor DNA and ctDNA. While a prior study demonstrated unsatisfactory correspondence, two limitations may have influenced the accuracy of these results: The median interval between the collection of tumor tissues and peripheral blood was 146 days, and ctDNA and tumor DNA were each sequenced using different platforms (Guardant360 and Foundation One) (Chae et al, 2017). Alternatively, Kaisaki et al analyzed genomic alterations of ctDNA and primary tumors in 21 melanoma patients and showed an ideal concordance between ctDNA and tumor DNA when samples were collected before treatment, confirming that the interval between sample of tissue and peripheral blood affects sequencing results (Kaisaki et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative analysis of ctDNA using ddPCR assays is performed on the basis of the correlation between disease stage and ctDNA:cfDNA concentration ratio . On the other hand, qualitative studies use NGS to examine ctDNA for variations in cancer hotspots or the entire genome to examine early‐stage disease, response to treatment and prognosis . Detection of single‐nucleotide variations is generally performed through sensitive methods such as BEAMing, Safe‐SeqS, TamSeq and ddPCR assays, while WGS is used to detect copy number variations (CNVs) and chromosomal instabilities .…”
Section: Liquid Biopsy Componentsmentioning
confidence: 99%
“…107 On the other hand, qualitative studies use NGS to examine ctDNA for variations in cancer hotspots or the entire genome to examine early-stage disease, response to treatment and prognosis. 108,109 Detection of single-nucleotide variations is generally performed through sensitive methods such as BEAMing, Safe-SeqS, TamSeq and ddPCR assays, while WGS is used to detect copy number variations (CNVs) and chromosomal instabilities. 102,110,111 Analysis of single-locus hotspots is achieved through ddPCR assays, 112,113 but this approach is limited when searching for a large number of variants or when looking for novel variants.…”
Section: Analysis Of Ctdna In Bloodmentioning
confidence: 99%